GE_GERICHTE C/18638/2013 vom 4. Dezember 2013 - GE Cour de justice (2013)
ASSOCIATION; LIQUIDATION(EN GÉNÉRAL); SUPPRESSION(EN GÉNÉRAL); RÉVOCATION(EN GÉNÉRAL); DÉCISION | ORC.165; ORC.153.A.2; ORC.153.B.2; ORC.153.B.3; ORC.152; ORC.17; ORC.15